2009
DOI: 10.1002/ejoc.200801285
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Galactosyltransferase Inhibitor with Diamino Sugar as a Pyrophosphate Mimic

Abstract: Conjugates of 2,4-diamino sugars and uridine have been synthesized as galactosyltransferase inhibitors. The relationship between inhibitory activity and the chelation abilility of the hinge-like diamino sugar towards a metal ion was studied by NMR spectroscopy. One of the conjugates exhib-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This is in line with our observations that the PglC reaction saturates at 30 % conversion, supposedly due to UMP product inhibition. Although uridyl‐phosphates are successfully elaborated towards potent glycosyltransferase inhibitors, in the long term, the amine‐substituted derivatives would be advantageous due to the positive charge, which would enhance cell permeability relative to negatively charged analogues, as has been an inspiration in several inhibitor design strategies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with our observations that the PglC reaction saturates at 30 % conversion, supposedly due to UMP product inhibition. Although uridyl‐phosphates are successfully elaborated towards potent glycosyltransferase inhibitors, in the long term, the amine‐substituted derivatives would be advantageous due to the positive charge, which would enhance cell permeability relative to negatively charged analogues, as has been an inspiration in several inhibitor design strategies …”
Section: Resultsmentioning
confidence: 99%
“…Although uridyl-phosphates are successfully elaborated towards potent glycosyltransferase inhibitors, [30][31][32] in the long term, the aminesubstituted derivatives would be advantageous due to the positive charge, which would enhancec ell permeability relative to negatively charged analogues, as hasb een an inspiration in several inhibitor design strategies. [33][34][35][36][37] Encouraged by these initial inhibition results, the mureidomimetics trategy was expandedt oc reate 'dyad inhibitors' that would display two binding modules. Instead of the alanine that had principally been incorporated to increase rigidity,atargeted screen was performed to identify am oiety that could potentially bind in the carbohydrate-binding site of the UDP-sugar substrate, and therefore our attentionw as focusedo n mono-a nd bicyclic aromatic compounds that could engage in p-stacking interactions often identified in sugar-binding sites.…”
Section: Strategy 1: Mureidomimeticsmentioning
confidence: 99%
“…At a concentration of 1.5-10 mg/mL, the chelating ability ranged from 5.2% to 58% for GLP L 1, while only from 4.2% to 21% of that for GLP L 2. It is suggested that the chelating activity may be related to the conformations of different polysaccharides [37]. The different conformations for GLP L 1 and GLP L 2 might be another factor to affect the chelating ability except the factor of different molecular weights.…”
Section: Ferrous Metal Ions Chelating Activity Of Glp L 1 and Glp Lmentioning
confidence: 99%
“…Their inhibitory capacity seems to depend on conformational flexibility and thus on the chelating abilities of the hinge-like diamino sugar towards a metal ion such as Mn 2+ within the structure of the enzyme 130 . Inhibition of mammalian β4-GalT1 and β3-GalT5 can also be obtained by the use of bivalent imidazolium salts up to 1 mM, which are not substrate analogues and can therefore inhibit other types of GalT too.…”
Section: Galactosylationmentioning
confidence: 99%